2012
DOI: 10.1016/j.jacc.2012.05.036
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Pulmonary Vein Isolation With Versus Without Concomitant Renal Artery Denervation in Patients With Refractory Symptomatic Atrial Fibrillation and Resistant Hypertension

Abstract: Renal artery denervation reduces systolic and diastolic blood pressure in patients with drug-resistant hypertension and reduces AF recurrences when combined with PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
260
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(270 citation statements)
references
References 23 publications
3
260
2
5
Order By: Relevance
“…In the future, novel approaches for ANS modulation could increase the efficacy of AF ablation treatment. 127,128,129 …”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, novel approaches for ANS modulation could increase the efficacy of AF ablation treatment. 127,128,129 …”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…279 Pooled analysis of two small studies demonstrated that renal artery denervation resulted in both sustained lowering of BP and reduction in AF recurrence postablation. 127,331 However, the antiarrhythmic effect of renal denervation is not well established, and whether it is mediated by remodeling of the hypertension-associated atrial substrate or decrease in neurohormonal activation remains uncertain. 129 Whereas upstream therapy with angiotensin-converting enzyme inhibitors and angiotensin receptor blockers might be effective for primary prevention of AF in patients with systolic LV dysfunction or left ventricular hypertrophy, 332 their effect on secondary prevention postablation of AF is uncertain.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
See 1 more Smart Citation
“…Early clinical evidence has suggested a possible benefit of RDN as an adjunct treatment option not just for VAs but for atrial fibrillation as well. 30,31) Study limitations: There are certain limitations in this study. First, norepinephrine spillover was not measured.…”
Section: Discussionmentioning
confidence: 97%
“…The perfect tactic for the handling of AF is rhythm control, but this is sometimes very hard to accomplish [3]. Pokushalov and colleagues [4] in recent times described that renal sympathetic denervation (RSD) reduces AF recurrences when joined with pulmonary vein isolation (PVI). Pointing of the pulmonary veins (PVs) and/or the PV antrum is the keystone for best AF ablation procedures.…”
Section: Introductionmentioning
confidence: 99%